Faktor-Faktor Yang Mempengaruhi Rendahnya Minat Pedagang Muslim Dalam Menggunakan Jasa Bank Syariah Mandiri KC Sumberrejo-Bojonegoro (GEMA EKONOMI, 2019)
ÃƒÆ’Ã†â€™ÃƒÂ¢Ã¢â€šÂ¬Ã…Â¡ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â This research aims to analyze the factors which influence the low interest of muslim traders in the use of services Bank Mandiri Syariah KCSumberrejo. Those factors are product knowledge, promotion, Religiosity, and perception. This research was conducted in Bank Mandiri Syariah (BSM) Sumberrejo Branch because it is the only Islamic Bank in the Sumberrejo Sub-district in this research is still classified as low devotees namely muslim traders in the market Sumberrejo as the target. This research is quantitative research using Survey Method. The sampling technique used was Purposive Sampling. Data collection was done by disseminating a questionnaire to 71 respondents with muslim traders who haven't criteria using Bank Mandiri Syariah KC Sumberrejo and interpretation of data using Multiple Linear regression analysis.Based on the results of the test T (partial test) can be inferred variable promotion and perception of the partially positive and significant effect against the low interest in muslim traders using services Bank Mandiri Syariah KC Sumberrejo, with value significance under the value alpha (ÃƒÆ’Ã†â€™Ãƒâ€¦Ã‚Â½ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â± = 0.05), whereas the variable product knowledge and Religiosity partially do not affect significantly to low interest in muslim traders using Bank Mandiri Syariah KC Sumberrejo, with value the significance of the above values of alpha (ÃƒÆ’Ã†â€™Ãƒâ€¦Ã‚Â½ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â± = 0.05). The most influential factor obtained the dominant factors in perception, i.e. it is based on the value t calculate the factor of perception (5.808) is greater than count, the t factor of knowledge products (0.070), promotion (2.388) factors, and religiosity (1.622-) so that It is evident that the dominant perception more influential factor when compared to the factor of knowledge products, promotions, and religiosity.ÃƒÆ’Ã†â€™ÃƒÂ¢Ã¢â€šÂ¬Ã…Â¡ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â Keyword: Low Interest, knowledge products, promotions, Religiosity, and perception.DOI : 10.5281/zenodo.3474598